Dynamic temperature modulation method of Ag-modified SnO2 sensor for the identification of different alcohol homologues - Meng, Fanli; Xu, Jiaao; Ji, Hanyang; Yuan, Kaiping; Yuan, Zhenyu (Sensors and actuators. B, Chemical, 2026)
Due to their structural similarity, alcohol homologues suffer from issues of cross-sensitivity and inaccurate discrimination in sensing detection, which limits their applications in food safety, chemical production, and other fields. In this study, a dynamic testing strategy based on Ag-SnO2 nanomaterials is proposed. Gas sensors with different Ag loadings were fabricated, and their resistance response curves under continuous temperature variation were recorded. A unique dual-valley pattern was observed in the high-temperature region, where the intensity of the second valley increases significantly with the growth of the carbon chain length of alcohols. Through in-depth analysis of the dynamic response characteristics of alcohol compounds, the correlation between these characteristics and the diffusion/adsorption properties of gas molecules was revealed, and a conjecture on the mapping relationship between carbon chain length and response patterns was proposed. By integrating dynamic parameter extraction with pattern recognition algorithms, this strategy achieves high-selective identification of alcohol homologues, providing theoretical and technical support for the design of high-performance gas sensors. [Display omitted] •Novel Ag-SnO2 dynamic sensing overcomes alcohol cross-sensitivity by analyzing current curves during temperature ramping.•A unique bimodal valley response intensity correlates with alcohol carbon chain length, revealing interaction mechanisms.•Fusing dynamic features enables highly selective alcohol identification via pattern recognition.